DNGR-1, a Dendritic Cell-Specific Sensor of Tissue Damage That Dually Modulates Immunity and Inflammation - Cueto, Francisco J.; del Fresno, Carlos; Sancho, David (Frontiers in Immunology, 2020)
DNGR-1 (encoded by CLEC9A) is a C-type lectin receptor (CLR) with an expression profile mainly restricted to type 1 conventional dendritic cells (cDC1s) both in mice and humans. This delimited expression pattern makes it appropriate for defining a cDC1 signature and for therapeutic targeting of this population, promoting immunity in mouse models. Functionally, DNGR-1 binds F-actin, which is confined within the intracellular space in healthy cells, but is exposed when plasma membrane integrity is compromised, as happens in necrosis. Upon F-actin binding, DNGR-1 signals through SYK and mediates cross-presentation of dead cell-associated antigens. Cross-presentation to CD8+ T cells promoted by DNGR-1 during viral infections is key for cross-priming tissue-resident memory precursors in the lymph node. However, in contrast to other closely related CLRs such as Dectin-1, DNGR-1 does not activate NFB. Instead, recent findings show that DNGR-1 can activate SHP-1 to limit inflammation triggered by heterologous receptors, which results in reduced production of inflammatory chemokines and neutrophil recruitment into damaged tissue in both sterile and infectious processes. Hence, DNGR-1 reduces immunopathology associated with tissue damage, promoting disease tolerance to safeguard tissue integrity. How DNGR-1 signals are conditioned by the microenvironment, and the detailed molecular mechanisms underlying DNGR-1 function have not been elucidated. Here, we review the expression pattern and structural features of DNGR-1, and the biological relevance of the detection of tissue damage through this CLR.